Analisis kuantitatif aluminium (III) menggunakan reagen alizarin red S dan jaringan neural tiruan (ANN) = Quantitative analysis of aluminium (III) ion using alizarin red S and artificial neural network - Nurul Izzaty Hassan,; Musa Ahmad, (Universiti Kebangsaan Malaysia, 2007)
A quantitative analysis for determination of Al3+ concentration in aqueous solution has been carried out using alizarin red S (ARS) as a reagent to form ARS-Al(III) complex. The analysis was conducted using UV-Vis spectrophotometry method. ARS-Al(III) complex showed a maximum absorption peak at wavelength of 484 nm and optimum pH 5. The photostability study showed a RSD value of 0.46 %. The repeatability study at two different concentrations of 0.2 ppm and 9 ppm was found to give RSD values of 1.07 % and 0.67 %, respectively. Cu2+ and Fe3+ cations at the ratio of 1:10 slightly interfered. The study showed a low interfering effect for almost all of the interfering anions except for F- at the ratio of 1:1 and 1:10. This system was found to give dynamic Al3+ concentration range of 0.1 - 1.0 ppm. ANN architectur with 23 hidden neurons, 40000 epochs and training rate of 0.001 has successfully extended the dynamic range of Al3+ concentration from 0.1 - 8.0 ppm. ARS reagent was successfully immobilized onto XAD 4 and showed a good optical response toward Al3+ ion.